HUBUNGAN SELF-EFFICACY TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI SMA NEGERI 2 RAMBAH HILIR KABUPATEN ROKAN HULU - Marzuki, Ali; Ramadi, Ramadi; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research problem lacks good self-confidence because thelearning results have less satisfactory values. This research aims to find out therelationship of self-efficiency to the learning results of physical education at State HighSchool 2 Rambah Hilir district of Rokan Hulu. The research method used is thecorrelational method. The population used as many as 60 students with total samplingtechniques. The tool uses data capture through a questionnaire and is analysed usingmoment product correlation. Test data analysis requirements using KolmogorovSmirnov's test that asymp sig. self-efficacy 0.331 and asympt sig. 0.257 when comparedwith sig. The results of the study show that there is a significant relationship betweenself-efficiency and the learning outcome of physical education (r count = 0,566, r table< 0,237). This study concluded that students with high levels of efficiency tend to havebetter learning outcomes compared to students with low levels of effectiveness.Keywords: Self-efficacy, PJOK Learning Results, Jasmani Learning